The microbiome in endometrial cancer: vaginal milieu matters - Govorov, Igor; Komlichenko, Eduard; Ulrikh, Elena; Dikareva, Elena; Pervunina, Tatiana; Vazhenina, Oksana; Dzharbaeva, Amina; Kalinina, Olga; Zaikova, Ekaterina; Razumova, Zoia; Mints, Miriam; Sitkin, Stanislav (Frontiers in Medicine, 2025)
Endometrial cancer remains one of the most common malignancies in women, and its incidence is particularly increasing in developed countries. Despite the well-known promotive role of excessive exposure to estrogen, many other details of the pathogenesis of endometrial cancer remain unknown. Recent studies have elucidated the emerging role of the resident microbiota in the progression of various diseases, including cancer. Next-generation sequencing demonstrated that the uterine cavity, previously considered sterile, contains a composition-rich microbiota. In this work, we determined the differences in the composition of the intrauterine microbiota between patients with endometrial cancer and its precursor—endometrial hyperplasia.